(untitled) (Italiano LinguaDue, 2019)
Il contributo documenta le tendenze linguistiche recenti nei quotidiani, sia cartacei che on line, relative al piano grammaticale. Negli ultimi decenni si è verificata una crescente differenziazione comunicativa e linguistica tra le testate, originata in buona parte dall’orientamento politico; essa investe soprattutto i piani del lessico e della sintassi/interpunzione e in misura minore il piano grammaticale. Quest’ultimo livello mostra una differenziazione soprattutto in relazione all’uso del discorso diretto, mentre l’orientamento politico, determinante per lessico e sintassi, interviene molto poco sul piano morfosintattico. Between standard, neostandard and substandard: changes in current newspapers The paper documents recent language trends in newspapers, both printed and online, related to grammar. In recent decades, there has been a growing communicative and linguistic differentiation between newspapers, largely due to political orientation; this mainly concerns the lexicon and syntax/interpretation and, to a lesser extent, grammar. This latter shows a differentiation above all in relation to the use of direct speech, while political orientation, which is decisive for lexicon and syntax, impacts very little on morphosyntax.